Selexipag: an oral, selective prostacyclin receptor agonist for the treatment of pulmonary arterial hypertension - Simonneau, Gérald; Torbicki, Adam; Hoeper, Marius M.; Delcroix, Marion; Karlócai, Kristóf; Galiè, Nazzareno; Degano, Bruno; Bonderman, Diana; Kurzyna, Marcin; Efficace, Michela; Giorgino, Ruben; Lang, Irene M. (The European respiratory journal, 2012)
In this phase 2 proof-of-concept study we examined the safety and efficacy of selexipag, an orally available, selective prostacyclin receptor (IP receptor) agonist, as a treatment for pulmonary arterial hypertension (PAH). 43 adult patients with symptomatic PAH (receiving stable endothelin receptor antagonist and/or a phosphodiesterase type-5 inhibitor therapy) were randomised three to one to receive either selexipag or placebo. Dosage was up-titrated in 200-μg increments from 200 μg twice daily on day 1 to the maximum tolerated dose by day 35 (maximum allowed dose of 800 μg twice daily). Change in pulmonary vascular resistance at week 17 expressed as a percentage of the baseline value was the primary efficacy end-point, and was analysed in the per protocol set first and then in the all-treated set to assess robustness of results. A statistically significant 30.3% reduction in geometric mean pulmonary vascular resistance was observed after 17 weeks' treatment with selexipag compared with placebo (95% confidence limits -44.7– -12.2; p=0.0045, Wilcoxon rank sum test). This was supported by a similar result from the all-treated set. Selexipag was well tolerated with a safety profile in line with the expected pharmacological effect. Our results encourage the further investigation of selexipag for the treatment of PAH.